Pemberdayaan Umkm Hasil Perikanan Guna Mengembangkan Pola Pikir Masyarakat - Dewi Indah; Merina Merina; Selly Novianti (National Conference for Community Service Project (NaCosPro), 2019)
Society Empowerment Program (SePORA) already implemented in Tanjung Riau District RW 02. The implementation last for 10 weeks. First, the committee made an observation to know the ability of the surrounding community, then do the implementation which the result is fish snack also teach them how to promote their product online. The purpose of this implementation is to develop the mindset of the Tanjung Riau community on the importance of education and develop kitchen skills by utilizing fishery product also can increase economic income in Tanjung Riau.